IgM Antibodies Can Access Cryptic Antigens Denied to IgG: Hypothesis on Novel Binding Mechanism - Law, Eric Chun Yiu; Leung, Danny Tze Ming; Tam, Frankie Chi Hang; Cheung, Kitty Kit Ting; Cheng, Naomi Hua Yin; Lim, Pak Leong (Frontiers in Immunology, 2019)
Antibodies are well-known protein mediators of immunity. IgM is the primordial member and the neglected sibling of the later-evolved and more proficient IgG in regard to their therapeutic and diagnostic use. Serendipitously, however, we found a paradox: While murine IgM antibodies specific for guanosine triphosphate (GTP) were able to recognize native guanylyl antigens found in primate or rat muscle tissues by immunofluorescence assays (which mimicked the auto-antibodies from autoimmune patients to skeletal or smooth muscle), the murine and human IgG counterparts failed. The results were replicated in cell-free direct binding assays using small latex microspheres decorated densely with GTP. The IgG antibodies could bind, however, if GTP was presented more spaciously on larger particles or as a univalent hapten. Accordingly, oligomerization of GTP (30-mer) destroyed the binding of the IgG antibodies but enhanced that of the IgMs in inhibition ELISA. We reason that, contrary to current belief, IgM does not bind in a lock-and-key manner like IgG. We hypothesize that whereas the intact and rigid antigen-binding site of IgG hinders the antibody from docking with antigens that are obstructed, in IgM, the two component polypeptides of the antigen-binding site can dissociate from each other and navigate individually through obstacles like the ancestral single-polypeptide antibodies found in sharks and camelids, both components eventually re-grouping around the antigen. We further speculate that polyreactive IgMs, which enigmatically bind to more than one type of antigen, use the same modus operandi. The findings call for a re-look at the clinical potential of IgM antibodies particularly in specific areas in cancer therapy, tissue pathology and vaccine design, where IgG antibodies have failed due to target inaccessibility.